Capacity-Preserved, Energy-Enhanced Hybrid Topology Management Scheme in Wireless Sensor Networks for Hazardous Applications. (8th December 2011) - Jawahar, A.; Radha, S.; Sharath Kumar, R.
Abstract : A wireless sensor network is composed of large number of sensor nodes and they are densely deployed in the field to monitor the environment, collect the data and route it to a sink. The main constraint is that the nodes in such a network have a battery of limited stored energy the network lifetime gets reduced. There are various topology management schemes such as SPAN, STEM, GAF, BEES and so forth, for improving network parameters such as capacity, lifetime, coverage and latency. These schemes do not improve all the mentioned network parameters. Sustainable Physical Activity in Neighbourhood (SPAN) scheme, preserves network capacity, decreases latency but provides less energy savings. Sparse Topology and Energy Management (STEM) scheme does not preserve capacity resulting in great energy savings and high latency. In the proposed scheme, new coordinator rule is implemented in SPAN, and then integrated with STEM. It is observed that the energy conserved increases by about 3.18% to 4.17% without sacrificing network capacity. Due to definite path in the proposed scheme the latency is reduced by almost half the latency of STEM scheme.